Telaah Historiografi Tafsir Indonesia - Lukman, Fadhli (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This article discusses the recent developments in the scholarship of (the history of) tafsir in Indonesia,especially with regards to how the writers in this scholarship built the terminology of tafsir nusantara that has been widely used lately. Furthermore, this paper offers an alternative way of discussing the terminology. Forthis purpose, this article methodologically and theoretically discusses the works within the discipline of the history of tafsir in Indonesia. This article argues that the term tafsir nusantara is used by in two perspectives:(1) as an instrument to limit the locus of research within the perspective of regional studies and (2) as anattempt at compiling and explaining the locality of tafsir; a derived view of Islam Nusantara. From these twoperspectives, this paper further discusses the terminology of tafsir nusantara through the perspective of tafsir as genealogical tradition.